2023
DOI: 10.1186/s40468-023-00227-3
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effect of computerized dynamic assessment and rater mediated assessment on EFL learners’ oral proficiency, writing performance, and test anxiety

Abstract: This study aimed to examine the impacts of computerized dynamic assessment (C-DA) and rater-mediated assessment on the test anxiety, writing performance, and oral proficiency of Iranian EFL learners. Based on Preliminary English Test (PET) results, a sample of 64 intermediate participants was chosen from 93 students. Running a convenience sampling technique, target test-takers were randomly divided into the experimental groups (C-DA) and control (rater mediated assessment). Following that, both groups had pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The objective of this case study was to investigate how interactionist discourse analysis (DA) could enhance the essay writing skills of ESL learners. DA is a flexible method that can be adapted to a variety of different teaching and learning environments to mediate student errors, in this case we focused on writing errors (Sherkuziyeva et al, 2023). The findings of the study revealed that DA was effective in mediating writing errors in each of the three students across all eight categories including vocabulary, subject-verb agreement, tenses, articles, active-passive voice conditionals, modal verbs, and coherence and cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this case study was to investigate how interactionist discourse analysis (DA) could enhance the essay writing skills of ESL learners. DA is a flexible method that can be adapted to a variety of different teaching and learning environments to mediate student errors, in this case we focused on writing errors (Sherkuziyeva et al, 2023). The findings of the study revealed that DA was effective in mediating writing errors in each of the three students across all eight categories including vocabulary, subject-verb agreement, tenses, articles, active-passive voice conditionals, modal verbs, and coherence and cohesion.…”
Section: Discussionmentioning
confidence: 99%